Cellular and humoral immunogenicity of recombinant Mycobacterium smegmatis expressing Ag85B epitopes in mice - Nur Ayuni, Kadir; Maria E, Sarmiento; Armando, Acosta (Elsevier Ltd, 2016)
Objective/background: The search for new vaccines more efficacious than bacille Calmette– Gue´ rin for tuberculosis prevention is of paramount importance for the control of the disease. The expression of Mycobacterium tuberculosis antigens in Mycobacterium smegmatis is one of the current strategies for the development of new-generation vaccines against tuberculosis. The objective of this study was to evaluate the immunogenicity in mice of M. smegmatis expressing epitopes from Ag85B antigen.